Conciliação judicial: uma abordagem crítica - Morais, Luis Carlos de (2016)
This research has the object of study the growing incorporation of methods that aim the achieving of solution of conflicts by consensus form into the justice system. In this direction, we can see a continuous doctrinal and normative effort directed to encourage the use of conciliation methods. Stands out, in normative terms, the issue of Resolution 125 of the National Council of Justice, that establishes the Judicial Policy of proper handling of conflicting of interests, and also the norms forecasted in the law 13,105 / 2015, which institutes the new Procedure Civil Code, among which the one that provides for a prior hearing dedicated exclusively to an attempt of conciliation. Given this framework, the aim of this research is, through bibliographic and empirical survey, to analyse the way it currently happen the attempts to establish a consensual solution to the conflict, specifically those in the midst of a judicial court through, using conciliation techniques and, by research, assure if the use of these means meets the main purpose of delivering a fair and appropriate legal result. The objective is to investigate factors that may compromise the use of the conciliation means as an alternative to a justcomposition of conflicts, preventing its work just to combine the interests of a judicial policy for outpouring of the system and its use as social accommodation tool.